WOMAN’S RIGHT DETERMINED BY BELLE’S ACTIONS IN "BEAUTY AND THE BEAST" BY GABRIELLE SUZANNE BARBOT - Nella Permata Hadi (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
Beauty and the Beast by Gabrielle Suzanne Barbot is a novel that tells the story of the love story of a beautiful girl named Belle and a creature with an ugly face. In every journey of their love there are many obstacles that stand in their way, in which one of the actions of a young man named Gaston. Gaston is someone who has high ambitions to possess Belle, which causes him to do various ways to win Belle's heart and steal Belle from the Beast. But Belle was never surrender, she did various ways to fail Gaston by taking various actions to get her right in choosing who she married and defeating Gaston. This study aims to discuss the actions of a woman who fight for her rights. Which is Belle is the main character in this research. Keyword : Beauty and The Beast, Woman’s Right, Belle